Metode Pengembangan Tema Sebagai Upaya Meningkatkan Kemampuan Siswa SMA Imelda Medan dalam Menulis Teks Argumentasi - Nurlela Nurlela; Rohani Ganie; Mahriyuni Mahriyuni; Muhammad Yusuf (Universitas Maritim AMNI Semarang, 2025)
In order to produce a good argumentative text that is easy for readers to understand, a skill is needed, one of which is writing skills. With the skill of writing argumentative texts, someone can develop critical thinking skills. In compiling an argument, someone must be able to analyze information, evaluate various points of view, and compile logical and consistent arguments. The partners involved in this program are students at SMA Imelda Medan where the main problem experienced by the partners is the lack of understanding of students in writing argumentative texts. Students can write this text but still do not meet the standards of argumentative texts such as the inability to identify a clear position or thesis, lack of logical reasoning, inability to structure the writing clearly. Therefore, the solution offered is to provide training in writing the text using a theme development approach. The location of this program is at SMA Imelda Medan which is located at Jl. Bilal, Medan, North Sumatra. This program consists of stages of preparation, implementation, monitoring, and evaluation. In implementing this community service, the team applied the in-house training method using a theme development approach. The students showed high enthusiasm in participating in the entire series of argumentative text writing training activities. The results of students' writing after the training showed an increase in the aspects of argument clarity, use of relevant evidence, and coherent paragraph arrangement. This success shows that the training was able to provide a positive impact in improving students' literacy skills in writing argumentative texts.